Blood Volume Changes Induced By Low-Intensity Intradialytic Exercise in Long-Term Hemodialysis Patients. Issue 2 (March 2016) - Ookawara, Susumu; Miyazawa, Haruhisa; Ito, Kiyonori; Ueda, Yuichiro; Kaku, Yoshio; Hirai, Keiji; Hoshino, Taro; Mori, Honami; Yoshida, Izumi; Morishita, Yoshiyuki; Tabei, Kaoru
Abstract : Intradialytic exercise-induced blood volume (BV) reduction may cause intradialytic hypotension in hemodialysis (HD) patients. However, BV recovery time after intradialytic exercise remains unknown. Hemodialysis patients were recruited, and their relative BV change (%ΔBV) were measured with intradialytic exercise (n = 12). After confirming the linearity of %ΔBV for 30 min, patients exercised using a stationary cycle in the supine position. The target exercise intensity was a 10% increase in heart rate (HR), corresponding to relatively low-intensity exercise. Baseline %ΔBV (assumed baseline) were calculated for the 30 min before exercise using linear regression analysis. The mean intradialytic exercise start and end times after HD initiation were 93.0 ± 8.4 and 116.4 ± 8.3 min, respectively, a mean exercise duration of 23.5 ± 2.6 min. Percentage change in blood volume declined rapidly upon exercise initiation and gradually increased above the assumed baseline throughout HD. At the end of HD, %ΔBV in the exercise group was significantly higher than the assumed baseline (measured – assumed baseline %ΔBV: 2.17 ± 0.62%; p = 0.02). Intradialytic exercise with low intensity in the supine position attenuated ultrafiltration-induced BV reduction at the end of HD. Therefore, intradialytic exercise may prevent intradialytic hypotension during later HD, although its intensity was relatively low level.